Alterations in the Tegument Surface of Adult Fasciola gigantica, After in vitro Treatment with the Crude Venom of Vespa orientalis - Abdelsater, Naser; Amer , Omar; Elshehaby , Mohammed; Mohamed , Sara (Journal of Advanced Veterinary Research, 2023)
The present study aimed to investigate the antiparasitic activity of the wasp venom (WV), Vespa orientalis, against the adult Fasciola gigantica (F. gigantica) worm, as WV has known pharmacological properties. We assessed its anthelmintic efficacy using 40 adult F. gigantica flukes collected from slaughtered cattle divided into four groups (10 each). Worms in three groups were treated with 50, 100, and 200 Âµg/ml of WV, while a fourth untreated one was used as control. After WV treatment, the tegument area of the flukeâ€™s body was assessed using a scanning electron microscope. This revealed several tegumental alterations all over the fluke’s body, including sunken spines due to local swelling, complete disappearance of spines from their sockets, furrowing and sloughing of the basal lamina, splitting off some spines to resemble an â€œopen jaw,â€ broken oral and ventral sucker teguments, increased swelling of the ventral sucker with loss of its ridges, severe swelling and smoothening of the ventral sucker due to loss of normal transverse ridges, deformed cirrus, and swollen sensory papillae with blebs. The sensory papillae were completely disrupted and dislodged, leaving pits and a series of holes throughout the basal lamina and severely eroded, turning into lesions exposing the basement membrane. These findings indicate that WV destructs the tegument surface of the adult flukes. However, further in vivo studies on the activity of WV treatment are recommended.